PENGARUH GLOBALISASI EKONOMI TERHADAP PERUBAHAN PERATURAN BIDANG PERJANJIAN DI INDONESIA - Priyono, Ery Agus (Fakultas Hukum, Universitas Diponegoro, 2018)
Indonesia, viewed from the historical aspect is in the cluster of Civil Law legal system brought by the Dutch during the Dutch East Indies colonial government. The colonial law of the Dutch East Indies operates as a national law based on the principle of concordance through Article II of the Transitional Rules that have been amended to become Article I of the Transitional Rules of the 1945 Constitution of the State of the Republic of Indonesia. However, along with the development of the situation, conditions, and real needs in the life of the state nowadays, the rules of the Civil Law legal system are perceived to have not been fully implemented. In practice today, in Indonesia, business practices arising out of the common law, Islamic law system alongside the customary law system of the archipelago. This paper aims to examine the figure of the future Law of Agreement, which is capable of responding to national and international challenges. The results of the study concluded that the National Pancasila-based Law Agreement will be able to answer the challenges of the era, both within the national scope of international / global.Keywords : national agreement law, globalization, Pancasila